2016
DOI: 10.5433/1679-0359.2016v37n6p4149
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pregnancy rates of Bos indicus cows subjected to different synchronization ovulation protocols using injectable progesterone or an intravaginal device

Abstract: This study evaluated the pregnancy rate in Nelore cows (Bos indicus) that were subjected to fixedtime artificial insemination (FTAI) using different protocols consisting of injectable progesterone (P4) or an intravaginal device (impregnated with P4). Multiparous cows 72-84 months in age, 30-45 days postpartum, were selected on the basis of the absence of a corpus luteum (CL) and follicles <8 mm after transrectal palpation and ultrasound examinations. On a random day of the estrus cycle (D0), the selected anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Recently, it was found that cows synchronized with the conventional protocol TAI (Control/CIDR) had a higher (P < 0.05) pregnancy rate (60%) than those synchronized with P4 injectable/TAI 36 hours (33.3%). However, the group receiving injectable P4/TAI 48 hours had a similar (P > 0.05) pregnancy rate (48.9%) to those treated with either the conventional protocol ( Campos et al ., 2016b ).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Recently, it was found that cows synchronized with the conventional protocol TAI (Control/CIDR) had a higher (P < 0.05) pregnancy rate (60%) than those synchronized with P4 injectable/TAI 36 hours (33.3%). However, the group receiving injectable P4/TAI 48 hours had a similar (P > 0.05) pregnancy rate (48.9%) to those treated with either the conventional protocol ( Campos et al ., 2016b ).…”
Section: Discussionmentioning
confidence: 82%
“…The use of injectable P4 for TAI has provided lower pregnancy rates in comparison to protocols with P4 devices ( Morotti et al ., 2013b ; Campos et al ., 2016b ). However, several positive aspects of injectable P4 have been encouraging new experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in both cows and heifers, the reuse of P4 devices have shown varied results depending on the breed, individual response, nutritional status, diet, and adopted hormonal combination (Pinto, Silva, Mota, & Alberton, 2009). Conversely, the use of injectable P4 in synchronization protocols has been related to low cost, easy management of animals, and hygienic benefits (Morotti, Campos, Oliveira, & Seneda, 2013a;Morotti, Campos, & Seneda, 2013b;Campos, Morotti, Bergamo, Costa, & Seneda, 2016a;Campos, Morotti, Costa, Bergamo, & Seneda, 2016b). For TAI programs, these benefits provide a reduction in the risk of health problems associated with intravaginal devices, such as loss of the device and the occurrence of vaginitis and vulvovaginitis (Morotti et al, 2013a(Morotti et al, ,b, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, a ação da P4 injetável ainda não está totalmente elucidada. Ainda assim, estudos tem demonstrado taxas de prenhez similares com protocolo utilizando P4 injetável e implante intravaginal (CAMPOS et al, 2016).…”
Section: Protocolos a Base De Estradiol E Progesteronaunclassified